Impact of Extra Curricular Training (Basketball and Athletics) on Muscle Strength in Boys 11-14 Years of Age - Arūnas Emeljanovas; Kristina Poderienė; Dario Novak (Lithuanian Sports University, 2018)
Research background and hypothesis. Human growth and maturation is determined by interaction of endogenous and exogenous factors. The most sensitive to the external influences is the age period between 11 and 14 years. The investigations of this age period in boys engaged in sports may reveal the complex interaction of the endogenous and exogenous factors. Hypothesis: Improvement of the muscle capacity indices in early adolescence depends on the nature of physical load. Research aim was to examine long-term extra curricular training in basketball games and athletics (sprint) effects on muscle strength of boys in early adolescence. Research methods. 105 boys - non-athletes (n = 35), athletes - sprint runners (n = 35) and basketball players (n = 35) - participated in the study. The boys were engaged in the chosen sports for no less than 2 years. The same cohorts were followed for four years at the age of 11, 12, 13 and 14 years. The strength of the arm levators, femoral flexors, calf extensors, calf flexors, forearm extensors and forearm flexors was measured using the dynamometer "Nicholas".  The  maximum  force  required  for  the  isometric  muscle  contraction  mode  was  obtained  when  the resistance, caused by the investigator, occurred. Research  results.  Dynamometry  assessments  between  the  groups  showed  that  the  muscle  strength  of  the athletes  -  sprint  runners  was  greater  than  that  of  non-athletes  and  basketball  players.  Statistically  significant differences between boys were identified in all age groups in assessment of both right and left sides. Discussion and conclusions. Improvement of the muscle capacity indices in early adolescence depends on the nature of physical load: the muscle strength indices increased more in the athletes - sprint runners than in the basketball players. Keywords: adolescence, dynamometry, sport.